THE AUTHENTIC ASSESSMENT TO MEASURE STUDENTS’ ENGLISH PRODUCTIVE SKILLS BASED ON 2013 CURRICULUM - Rukmini, Dwi; Saputri, Lenggahing Asri Dwi Eko (Indonesian Journal of Applied Linguistics, 2017)
In 2013, the Indonesian Ministry of Education and Culture published the 2013 Curriculum which demands teachers to implement authentic assessment as the method of assessing the students’ competence. There were three areas of students’ competence that should be assessed by authentic assessments, namely attitudes, knowledge, and skills. The types of authentic assessment that could be used to assess students’ skills are performance, project, and portfolio. This study aims at describing the implementation of authentic assessment to measure students’ English productive skills based on 2013 Curriculum at the eighth grade of a pilot school--State Junior High School 1 Ungaran (SJHS1U) in the academic year 2015/2016, explaining the problems the teachers encountered in implementing it, and explaining the solution used by the teachers to overcome those problems. The data were collected through interviews, class and document observations, were validated by triangulation of sources and analysed by using the flow model of Miles and Hubberman (1984). The results of the study revealed that the English teachers of the school have implemented the authentic assessment to measure students’ English productive skills. In doing so, the teachers asked the students to describe picture cues and retell the story as the performance assessments, to write a text for the portfolio assessment and to produce a comic for the project assessment. However, the implementation has not been conducted properly yet.